Application of musyarakah in Islamic banking - Sarpini Sarpini (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2019)
Purpose - The purpose of this study is to explain syirkah, one of the popular profit-sharing scheme.Method - This research is a descriptive analysis that describes all data and then analyzes the data to obtain a conclusion.Result - This study concludes that the legal basis of syirkah is Al-Qur'an, Sunnah, ijma 'and its application in Islamic banking, namely project financing and venture capital.Implication – Understanding one of the implementation of the profit-sharing system mostly keeps the principle of justice running in the economy.Originality - This study is essential to continue to be studied and explored considering there are still many issues of Islamic law (muamalah) that need to be resolved in sharia law.